2020
DOI: 10.1007/s10476-020-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

No Entire Inner Functions

Abstract: We study generalized inner functions on a large family of Reproducing Kernel Hilbert Spaces. We show that the only inner functions that are entire are the normalized monomials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In a recent paper, Cobos and Seco [13] showed that under several additional assumptions, the only entire inner functions on đ» 2 đ‘€ are multiples of monomials. It turns out that this result remains true on all đ» 2 đ‘€ , as we show here.…”
Section: Inner Functions and Linear Combinations Of Kernelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, Cobos and Seco [13] showed that under several additional assumptions, the only entire inner functions on đ» 2 đ‘€ are multiples of monomials. It turns out that this result remains true on all đ» 2 đ‘€ , as we show here.…”
Section: Inner Functions and Linear Combinations Of Kernelsmentioning
confidence: 99%
“…Consider a weighted Hardy space Hw2$H^2_{w}$, where w=false{wkfalse}kâ©Ÿ0$w=\lbrace w_k\rbrace _{k\geqslant 0}$ consists of positive real numbers with limk→∞wkwk+1badbreak=1.\begin{equation*} \lim _{k\rightarrow \infty }\frac{w_k}{w_{k+1}}=1. \end{equation*}In a recent paper, Cobos and Seco [13] showed that under several additional assumptions, the only entire inner functions on Hw2$H^2_w$ are multiples of monomials. It turns out that this result remains true on all Hw2$H^2_w$, as we show here.…”
Section: Analogues Of Finite Blaschke Productsmentioning
confidence: 99%